Radiation induced emulsion grafting of glycidyl methacrylate onto high density polyethylene: a kinetic study - Nasef, Mohamed Mahmoud (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
Emulsion graft polymerisation of glycidyl methacrylate monomer onto high density polyethylene (HDPE) resin was studied. The radicals required to initiate the reaction were produced in HDPE resin by irradiation with the electron beam accelerator at ambient and vacuum conditions. The grafting reaction of GMA with irradiated HDPE was initiated by emulsion method using Tween 20 as a surfactant and water as a solvent under controlled conditions. The kinetic behavior of grafting reaction was investigated with respect to the degree of grafting under various parameters i.e. monomer concentration, radiation dose, grafting temperature and surfactant concentration. The degree of grafting was found to be a function of the investigated parameters. Particularly, surfactant concentration in the emulsion was found to be crucial for determining the micelle size and eventually the degree of grafting. The order of dependence of the initial rate of grafting on the monomer concentration and the irradiation dose was found to be 0.94 and 0.60, respectively. The initial rate of grafting was also found to increase with the increase in the grafting temperature varied in the range of 308-333 K. The optimum reaction parameters required to obtain desired and reproducible degrees of grafting in the resin could be identified. Moreover, the emulsion radiation grafting method was found to offer essential advantages over the conventional grafting with solvents including low radiation dose, less monomer concentration and cost effectiveness.